Respuesta :

Answer:

1

Step-by-step explanation:

Assuming, we want to find the value of [tex]((-14)^0)^{-2}[/tex]

Recall that: any non-zero number exponent zero is 1.

Using this property, we simplify our expression to [tex](1)^{-2}[/tex] since [tex](-14)^0=1[/tex]

Now using the property of exponents: [tex]a^{-n}=\frac{1}{a^n}[/tex]

This implies that:[tex]1^{-1}=\frac{1}{1^2}=\frac{1}{1}=1[/tex]

The correct answer is 1

Answer:

The anwser in the edge is 1.

Step-by-step explanation:

ACCESS MORE